STRATEGI KOMUNIKASI DINAS KESEHATAN KOTA PEKANBARU DALAM MENSOSIALISASIKAN GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) DI KOTA PEKANBARU - Ulandari Erisa; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Currently no infectious diseases increased (PTM) such as jantuk attacks and stroke, cancer, high blood, lung and asthma-like breathing then diabetes and others.Still the low level of awareness of public health, are often the cause of the emergence of a wide range of issues related to public health, low public awareness is due to several factors.In this case the health service of the city of Pekanbaru, conducting socialization movement society healthy living (GERMAS).The purpose of this research is to know the audience analysis, planning and media selection conducted Health Office pekanbaru in disseminating the healthy communities movement alive in the city of pekanbaru.This study used descriptive qualitative research method that is by describing the state of the subject and object of research, at this time based on the facts that exist.singer research informant hearts totaled 7 informant and its taken by purposive. The types and sources of data used are primary data and secondary data. Technique of collecting interview data and documentation. Data analysis techniques use interactive data analysis models. The technique of checking the validity of the data uses an extension of participation and triangulation.Research show that the development communication strategies of Pekanbaru City Health Office has a goal in disseminating the healthy living society movement, namely the whole sociality of Pekanbaru in terms of education, institutions, businesses, individuals, families, age and gender. Planning massages used directly to the core of the message through three format of organizing messages that topical format, special format and problem solving, message style and appeal. After that the use of the selected media is face to face (directly), print media, electronic media and outdoor media.Keybord: Srategy, communication, socialize